KEMAMPUAN MENULIS RANGKUMAN BUKU ILMU PENGETAHUAN POPULER SISWA KELAS IX SEMESTER GANJIL SMP PANGUDI LUHUR BANDAR LAMPUNG TAHUN PELAJARAN 2013/2014 - Jaya, Ery Nurma; Rachmasisca, Frieska Maryova (LPPM STKIP PGRI Bandar Lampung, 2014)
This study aims to identify and describe the ability to write a summary of popular science books, as well as to determine the obstacles to writing a summary of the popular science books, especially the students of class IX Junior High School of Pangudi Luhur Bandar Lampung academic year 2013/2014.The method used in this research is descriptive quantitative. Meanwhile, the population in this study were all students of class IX Junior High School of Pangudi Luhur Bandar Lampung academic year 2013/2014. While the data collection, this study took 30 students sampled from the population using a random sampling technique.From the results of the data that has been analyzed, known to the average value and the average ability level of students as a whole and per indicator, in summary writing popular science books. Overall, the average value (was 59 and the average level of capability that is in the medium category. Whereas, the average value and the average ability level of students per each indicator are: (1) a summary of the language indicator: = 37 and the average level of ability in the low category, (2) a summary indicator of the suitability of the content of the book: = 56 and the average ability level in the medium category, (3) indicators completeness of the content: = 93 and the average ability level in the category very good, (4) the indicator word choice / diction: = 68 and the average level of ability in both categories, (5) sentence structure indicators: = 52 and the average ability level in the medium category, (6) indicators of the correct use of spelling and punctuation: = 49 and the average level of ability in the low category.